Ballistic resistance and energy absorption of honeycomb structures filled with reactive powder concrete prisms. (September 2017) - Jin, Xiaochao; Jin, Tao; Su, Buyun; Wang, Zhihua; Ning, Jianguo; Shu, Xuefeng
Two kinds of innovative re-entrant and hexagonal cell honeycomb sandwich structures filled with reactive powder concrete were proposed, and the ballistic resistance and energy absorption of the sandwich structures were investigated by numerical simulations. The deformation and failure modes of the different structures were analyzed and evaluated in detail. The honeycomb sandwich structures filled with reactive powder concrete prisms improved the capacity of ballistic resistance and energy absorption significantly, compared to the normal reactive powder concrete plates and sandwich structures without reactive powder concrete prisms. The analysis shows that the auxetic re-entrant cell honeycomb sandwich structures have a better ballistic performance than the hexagonal cell honeycomb sandwich structures. The sandwich structures were subjected to impact by three kinds of projectiles: flat, hemispherical and conical nosed. The ballistic limit of the flat nosed projectile is the highest, while the impact performance of the conical and hemispherical nosed projectiles is obviously different from the flat nosed projectile, especially in a relative high velocity range. The sharper nose leads to a higher value of exit velocity and mass loss. In addition, effects of different design parameters on ballistic resistance were also studied by changing the thickness of honeycomb cell and face plates. Results indicate that the thickness of honeycomb walls and face plates have significant effect on the ballistic resistance and energy absorption in a relative low velocity range, while there are no big differences when the initial impact velocity exceeds 400 m/s.